Detection of Klebsiella pneumoniae in raw vegetables using most probable number-polymerase chain reaction (MPN-PCR) - Puspanadan, Soopna; Loo, Yuet Ying; Nillian, Elexson; Kuan, Chee Hao; Goh, Sur Guat; Chang, Wei San; Lye, Ying Ling; Afsah-Hejri, Leili; Tang, John Yew Huat; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; et al. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Klebsiella pneumoniae (K. pneumoniae) is one of the most important members of Klebsiella genus in Enterobacteriacae family, which is responsible for pneumonia (the destructive lung inflammation disease). Vegetables are known as source of contamination with K. pneumonia. Raw vegetables are usually consumed in salads and other dishes. The aim of this study was to investigate the occurrence of K. pneumoniae in raw vegetables marketed in Malaysia. Two hundred commonly used salad vegetables (lettuces, parsley, cucumber, tomato and carrot) from hypermarkets and wet markets were investigated for presence of K. pneumoniae using Most Probable Number-Polymerase Chain Reaction (MPN-PCR). K. pneumoniae was found to be significantly more frequent (100%) and (82.5%) in lettuce and cucumbers, respectively. K. pneumoniae contamination was lowest in carrot samples (30%). All samples were contaminated with K. pneumoniae ranging from <3 to 1100 MPN/g. Results showed the high health risk associated with consumption of raw vegetables.